Identification of Weissella species by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - Lee, Meng-Rui; Tsai, Chia-Jung; Teng, Shih-Hua; Hsueh, Po-Ren (Frontiers in Microbiology, 2015)
Although some Weissella species play beneficial roles in food fermentation and in probiotic products, others such as W. confusa are emerging Gram-positive pathogens in immunocompromised hosts. Weissella species are difficult to identify by conventional biochemical methods and commercial automated systems and are easily misidentified as Lactobacillus and Leuconostoc species. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is increasingly being used for bacterial identification. Little, however, is known about the effectiveness of MALDI-TOF MS in identifying clinical isolates of Weissella to the species level. In this study, we evaluated whether the MALDI-TOF MS Bruker Biotyper system could accurately identify a total of 20 Weissella confusa and 2 Weissella cibaria blood isolates that had been confirmed by 16s rRNA sequencing analysis. The MALDI-TOF Biotyper system yielded no reliable identification results based on the current reference spectra for the two species (all score values <1.7). New W. confusa spectra were created by randomly selecting 3 W. confusa isolates and external validation was performed by testing the remaining 17 W. confusa isolates using the new spectra. The new main spectra projection (MSP) yielded reliable score values of >2 for all isolates with the exception of one (score value, 1.963). Our results showed that the MSPs in the current database are not sufficient for correctly identifying W. confusa or W. cibaria. Further studies including more Weissella isolates are warranted to further validate the performance of MALDI-TOF in identifying Weissella species.